Involvement of Gaba and Cannabinoid Receptors in Central Food Intake Regulation in Neonatal Layer Chicks: Role of CB1 and Gabaa Receptors - Zendehdel,M (2017)
ABSTRACT Feeding behavior is regulated via a complex network which interacts via diverse signals from central and peripheral tissues. Endocannabinoids modulate release of GABA in a variety of regions of the central nervous system. Endocannabinoids and GABAergic system have an important role in the central regulation of appetite. Thus, the present study examines the possible interaction of central canabinoidergic and GABAergic systems on food intake in 3-h food-deprived (FD3) neonatal layer-type chicks. The results of this study showed that intracerebroventricular (ICV) injection of 2-AG (2-Arachidonoylglycerol, selective CB1 receptors agonist, 2µg) significantly increased food intake and this effect of 2-AG was attenuated by Picrotoxin (GABAA antagonist, 0.5µg) (P<0.001); but 21ng CGP54626 (GABAB antagonist) had no effect (p>0.05). Also, hyperphagic effect of CB65 (CB2 receptors agonist, 1.25µg) was not affected by Picrotoxin or CGP54626 (p>0.05). Moreover, the food intake of chicks was significantly increased by ICV injection of GABAA agonist (Gaboxadol, 0.2 µg) and SR141716A (CB1 receptors antagonist, 6.25µg) significantly decreased Gaboxadol-induced hyperphagia (P<0.001) but CB2 receptors antagonist (AM630, 1.25µg) had no effect. In contrast, co-injection of SR141716A or AM630 with GABAB agonist (baclofen, 0.2µg) had no effect on the hyperphagia induced by baclofen (p>0.05). These data showed there might be an interaction between central cannabinoidergic and GABAergic systems via CB1 and GABAA receptors in control of food intake in neonatal layer chicks.